Communication and social identity dynamics in UAE organizations - Willemyns, M.; Hosie, Peter; Lehaney, B. (World Business Institute, 2011)
This research focuses on cross-cultural communication in the workplace between United Arab Emirates Nationals (Emiratis) and western expatriate employees. Communication Accommodation Theory and Social Identity Theory were the major theoretical frameworks used, to examine how Emirati employees perceived expatriate employees in terms of either “ingroups” or “outgroups”. 192 Emiratis (158 males and 34 females) from a variety of organizations in Dubai completed questionnaires in which they described an interaction they recently had with a western expatriate co-worker. The results indicated that miscommunications and negative perceptions invoked Emiratis’ perceptions of social distance from their western co-workers; that is, negatively perceived co-workers were categorized in negative outgroup stereotypes. However, many Emiratis reported positive communication with their expatriate co-workers. These respondents perceived their interactants at a more individualistic level, as opposed to categorizing them as a member of a stereotypical cultural outgroup. Given the rapid globalization of the workforce in the Middle-East, this study contributes towards a better understanding of cross-cultural communication between Arabs and westerners in a workplace context. Individuals from different nationalities, religions and values need to adopt a more inclusive approach to communicating with each other, to enable a shared a common identity and purpose when working shared towards organizational goals.